THE EFFECT OF HUMAN RESOURCE PLANNING IN STRENGTHENING THE ORGANIZATIONAL IMMUNITY OF NON-GOVERNMENTAL ORGANIZATIONS: AN APPLIED STUDY ON (MTS) - Lecturer Dr. Labeeb Ali Hussein (Scholars Digest Publishing, 2025)
The study examines the impact of human resource planning strategies on strengthening organizational immunity in MTS, one of the leading telecommunications organizations in Russia. Particular attention is paid to the study of methods that contribute to the company's resilience to external and internal threats in the context of digitalization and rapidly changing market realities. case study and analysis of corporate reporting to identify factors affecting organizational efficiency and adaptability. The results of the study can be useful for other large companies seeking to improve sustainability and develop human resources in the face of digital transformation.
Keywords: Organizational immunity, human resource planning, digitalization, telecommunications, MTS, organizational stability, management strategies, adaptability.